Evaluation of Integrated Primary Care (ILP) Implementation: A Qualitative Assessment of Input and Process Dimensions in Banjarbaru City Health Centers - Anggun Wulandari; Neka Erlyani; Fauzie Rahman; Nur Laily; Andini Octaviana Putri; Lia Anggraini; Siti Maimunah; Sri Wulandari; Nuralpisah Nuralpisah; Fitrya Hayati Alkamaliah (Journal of Health and Nutrition Research, 2026)
Primary health care is the foundation of the health system with a focus on promotion and prevention. To strengthen this, the Indonesian Ministry of Health launched Integration Primary Care (ILP) policy in 2023, although its initial implementation faced various obstacles. This study aims to assess the input (human resources, infrastructure, and funding) and process (planning, organizing, implementing, and evaluating policies) dimensions of ILP implementation in Banjarbaru City Health Centers. The study used a descriptive qualitative approach with 20 informants consisting of health center heads and program managers in 10 health centers through purposive sampling. Data were collected through focus group discussions. Validity was tested using source and technique triangulation. This study uses an evaluative approach based on Azwar's (1996) health systems theory, which allows for a comprehensive analysis of the input and process components in ILP implementation. The results showed that ILP was still constrained by limited human resources, especially the limited core implementing staff and ILP supporting infrastructure does not fully meet standards. However, adaptive strategies such as cluster role sharing, cross-sector collaboration, and community involvement supported the policy's sustainability. In terms of process, planning, organization, implementation, and evaluation were carried out, but were still influenced by old mechanisms and minimal budgetary and organizational support. This study provides an understanding of ILP implementation in Primary Health Centers by highlighting systemic barriers and local strategies. This study concludes that there is a need for preparedness for the procurement and distribution of strategic medical devices, particularly screening tools and basic services, as well as strengthening the guidance, monitoring, and evaluation of ILP implementation periodically through technical assistance